DEVELOPMENT OF THE CONSTRUCTION OVERGROUND HYDRANT: Array - Kurtov, O.; Stylyk, I.; Benedyuk, V.; Chuyan, V. (Municipal economy of cities (Technical science), 2019)
Domestic industry currently produces underground fire hydrants, which are installed on the water supply networks in the inspection plumbing wells. The presence of a water well significantly increases the construction of the water supply network. True, in many cases there is no great need to create such wells. Moreover, when tracing a water supply network in the green zones of settlements, wells with hydrants in winter and at night is difficult to detect. This can be explained by the fact that overseas widespread use of over-the-top warheads was obtained abroad. As a result of the research carried out, the design of a overground hydrant, consisting of two main parts, was created: above ground - with nozzles for connecting hose lines and hydrant control units; underground, in which the hydrant shut-off node is located, and the system of water drainage remaining after the work of the hydrant. In order to compare the characteristics of the developed overhead hydrant and underground hydrant according to EN 14339: 2016, experimental studies have been carried out and found that a significant change in the water flow in the hydrant according to EN 14339: 2016 occurs in the range n '= 0.05 to n = 0.35 ( 80% of expenses). In the interval nx = 0,05, the flow through the hydrant is absent, as it also disturbs the seal of the rubber gasket of the gate. In a overground hydrant, a significant change in the flow of water occurs in the range nx = 0,02 to ne = 0,7 (80% of the charge), with nx = 0,25 the flow through the hydrant does not exceed 10% of the nominal. In addition, for the hydrant according to EN 14339: 2016, it is determined that the throughput is 45 liters per second, and for the proposed design of the overground hydrant - 67 liters per second. Thus, the capacity of the new hydrant is 1.5 times higher than the existing underground samples. Further research should be aimed at determining the possibility of a hydraulic shock in the hydrant, as well as confirmation of the economic efficiency of the introduction of such hydrants.